2002
DOI: 10.1002/1099-0682(200211)2002:11<2965::aid-ejic2965>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Dinuclear Manganese(III,III) Complex with Three Phenolate Ligands

Abstract: A dinuclear manganese complex ([Mn 2 L(µ-OAc) 2 ]PF 6 ) has been synthesized, where L is the trianion of 2,6-bis{[(2-hydroxy-3,5-di-tert-butylbenzyl)(2-pyridylmethyl)amino]-methyl}-4-methylphenol, a ligand with three phenolate groups. The two pseudo-octahedrally coordinated Mn ions are bridged via the two bidentate acetate ligands and the 4-methylphenolate group of the ligand. We have characterized the complex with electrochemistry, spectroelectrochemistry and EPR spectroscopy. Electrochemically the Mn 2 III,I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 6 publications
9
52
0
Order By: Relevance
“…Sun and co-workers [78] used the dianionic ligand 2,2′-bipyridine-6,6′-dicarboxylic acid (bda) to prepare the neutral mononuclear Ru WOC, [Ru(bda)(pic) 2 ] (52, Chart 12) that shows an excellent catalytic performance in both thermal and visible light-driven water oxidation [79,80]. The strong electron donating ability of the carboxylate ligands stabilizes the higher oxidation states of the metal center [81], making isolation of high valence intermediates possible. By mass spectrometry, two isolated oxidation states were identified as 52a and 52b (Chart 12).…”
Section: Ruthenium Complexes With Anionic Ligandsmentioning
confidence: 99%
“…Sun and co-workers [78] used the dianionic ligand 2,2′-bipyridine-6,6′-dicarboxylic acid (bda) to prepare the neutral mononuclear Ru WOC, [Ru(bda)(pic) 2 ] (52, Chart 12) that shows an excellent catalytic performance in both thermal and visible light-driven water oxidation [79,80]. The strong electron donating ability of the carboxylate ligands stabilizes the higher oxidation states of the metal center [81], making isolation of high valence intermediates possible. By mass spectrometry, two isolated oxidation states were identified as 52a and 52b (Chart 12).…”
Section: Ruthenium Complexes With Anionic Ligandsmentioning
confidence: 99%
“…A Mn V @O moiety has been proposed to play a key-role in OAO bond formation in photosynthesis as well as a model complex [9][10][11]. It is therefore of interest to study and characterize highvalent dinuclear manganese complexes, and we and others have prepared a number of dinuclear manganese complexes, which have oxidation states between Mn II and Mn IV and a varied number of coordinating phenoxy groups, which could be expected to stabilize high oxidation states of manganese [12][13][14][15][16][17][18]. These studies include the dinuclear Mn II,III complex 3, which was first prepared by Hendrickson et al [19] This complex was found to give a fairly stable Mn III,IV complex, which, however, appears to decompose on further oxidation [20,21].…”
mentioning
confidence: 99%
“…We performed stepwise electrolysis and EPR to characterize all these redox states. One-electron reduction resulted in an antiferromagnetically coupled Mn~ ull species as described above for 9 and 10 [39]. In contrast, by two-electron reduction a so far stmcturally noncharacterized species was formed that displays a very well structured 23-to 25-1ine EPR spectmm (Fig.…”
Section: Electrochemistry and Eprmentioning
confidence: 68%
“…From a series of synthesized dinuclear Mn comp|exes, we present here comptexes 9-11 shown in Fig. 4 [35][36][37][38][39].…”
Section: Mn Dimers and Their Electro-and Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation